Study on Staphylococcal Species Detected in Digestive Tract of Beavers (Castor fiber) and Their Variability with Properties - Andrea Lauková; Jana Šcerbová; Anna Kandricáková; Renata Miltko; Grzegorz Belzecki; Monika Pogány Simonová (Research Aspects in Agriculture and Veterinary Science Vol. 1, 2021)
Objective: Staphylococci from beaver`s gut (Castor fiber) were analyzed as a contribution in the basic microbiology as well as in the part of beaver`s microbiome study. Methodology: Free-living beavers (12), both male and female (aged 4-5 years) were caught with a net in north-east part of Poland Województwo (Provincie) Podlaskie Gmina-Wizajny, GPS:22º 52E:54º22N and placed in wire cages. Sampling was provided in Poland. Sampling of jejunum (12), colon (12) and caecum (6) was followed the ethic rules for animal handling. Results: Staphylococci detected in jejunum reached amount 2.73 ± 1.16 cfu/g (log 10) on average; their counts in caecum reached 1.87 ± 0.37 cfu/g on average and in colon 2.89 ± 1.70 cfu/g. After score evaluation using MALDI-TOF mass spectrometry, a high variability in staphylococcal species distribution in beaver`s gut was found; in total, including 18 identified strains, nine species were detected belonging into five clusters; the strains were allotted in the coagulase-negative staphylococcal species. The most frequently detected species were S. hominis and S. haemolyticus (five strains for each). The other species included two strains-S. epidermidis and S. lentus, S. pasteuri, S. cohnii, S. vitulinus, S. warneri, S. xylosus, one strain for each one species. Fifteen strains were deoxyribonuclease and almost haemolysis negative. Ten strains (not depending on the species) showed low-grade biofilm ability formation. Most of strains were methicillin susceptible with high production of lactic acid. Conclusion: The study is original contribution in staphylococcal microbiome of beavers and gives opportunity in more detail study of individual strain species.